2010
DOI: 10.1002/jat.1514
|View full text |Cite
|
Sign up to set email alerts
|

Developmental disruptions induced by insect growth regulator (Novaluron) in Bufo melanostictus tadpoles

Abstract: Novaluron is an insect growth regulator (IGR) used against fruit-borers and domestic pests. In this study, effects of different concentrations (0.5, 0.75, 1.0, 1.5 microg l(-1)) of novaluron on the tail regeneration, limb development and metamorphosis were examined in Bufo melanostictus. Thyroxine (1.0, 2.0, 3.5, 5.0 microg l(-1)), which promotes amphibian development/metamorphosis, and vitamin A (5, 20, 40, 60 IU l(-1)), which disrupts development and induce polymelia, were used for comparison. Bufo melanosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Delay in the appearance of limbs and completion of metamorphosis resulting into smaller-sized metamorphs noted in this study was also observed in our earlier studies in which the developing eggs were exposed to insect growth regulator novaluron, suggesting that the pesticides may intervene with thyroid hormone receptors (Pancharatna et al 2010). Our results are in accordance with those reported for Rana arvalis eggs to -cypermethrin (Greulich and Pflugmacher 2003).…”
Section: Discussionsupporting
confidence: 94%
“…Delay in the appearance of limbs and completion of metamorphosis resulting into smaller-sized metamorphs noted in this study was also observed in our earlier studies in which the developing eggs were exposed to insect growth regulator novaluron, suggesting that the pesticides may intervene with thyroid hormone receptors (Pancharatna et al 2010). Our results are in accordance with those reported for Rana arvalis eggs to -cypermethrin (Greulich and Pflugmacher 2003).…”
Section: Discussionsupporting
confidence: 94%